1997
DOI: 10.1002/(sici)1097-0274(199710)32:4<423::aid-ajim16>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Metalworking fluid-associated hypersensitivity pneumonitis: A workshop summary

Abstract: A workshop discussing eight clusters of hypersensitivity pneumonitis in the automotive industry among metalworking fluid‐exposed workers concluded that a risk exists for this granulomatous lung disease where water‐based fluids are used and unusual microbial contaminants predominate. Strong candidates for microbial etiology are nontuberculous mycobacteria and fungi. Cases of hypersensitivity pneumonitis occur among cases with other work‐related respiratory symptoms and chest diseases. Reversibility of disease h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 21 publications
5
91
2
3
Order By: Relevance
“…Moreover, we have recently demonstrated that dumping, cleaning, and recharging MWF systems are of little use to rid the MWF systems of microbial problems [5]. Several studies of respiratory disease among workers in contact with soluble MWF have suggested that Mycobacteria are associated with Hypersensitivity pneumonitis (HP) outbreaks [6][7][8][9][10]. Mycobacteria are ubiquitous in water environments (drinking water, pools, cooling towers) [11,12] and are amplified in MWF systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have recently demonstrated that dumping, cleaning, and recharging MWF systems are of little use to rid the MWF systems of microbial problems [5]. Several studies of respiratory disease among workers in contact with soluble MWF have suggested that Mycobacteria are associated with Hypersensitivity pneumonitis (HP) outbreaks [6][7][8][9][10]. Mycobacteria are ubiquitous in water environments (drinking water, pools, cooling towers) [11,12] and are amplified in MWF systems.…”
Section: Introductionmentioning
confidence: 99%
“…Workers using water soluble metalworking fluid (MWF) are exposed to a variety of chemical and biological agents that might be associated with the development of respiratory disease, including rhinitis. Many studies have focused on respiratory diseases such as occupational asthma, decrement of lung function, and hypersensitivity pneumonitis 1,[5][6][7][8][9] . These studies reported prevalence of a few nasal symptoms in workers exposed to MWF, but other respiratory symptoms or diseases were mainly discussed.…”
mentioning
confidence: 99%
“…HP has been described as occurring at facilities performing a variety of machining operations; 15,16 in general those facilities have used water-based MWF. 17 In many cases, the specific agent(s) responsible for HP and other illnesses is (are) not known. HP (also called extrinsic allergic alveolitis) is a spectrum of granulomatous, interstitial lung diseases which occur after repeated inhalation and sensitization to a wide variety of microbial agents (bacteria, fungi, amoebae), animal proteins, and low-molecular weight chemical antigens.…”
Section: Mwf Aerosol and Respiratory Illnessmentioning
confidence: 99%
“…The presence of Mycobacteria has been associated with many of the reported outbreaks of HP in machining environments. 17,18 The Mycobacteria isolated from TRW (as discussed above and in Results) was initially identified as M. chelonae, a mycobacteria that has been found as a contaminant in other machining plants where there have been outbreaks of HP. Recently M. immunogenum has been identified as new species of the M. abscessus/M.…”
Section: Mwf Aerosol and Respiratory Illnessmentioning
confidence: 99%